Female board representation and corporate acquisition intensity. (4th November 2014) - Chen, Guoli; Crossland, Craig; Huang, Sterling
Abstract : This study examines the impact of female board representation on firm‐level strategic behavior within the domain of mergers and acquisitions (M&A). We build on social identity theory to predict that greater female representation on a firm's board will be negatively associated with both the number of acquisitions the firm engages in and, conditional on doing a deal, acquisition size. Using a comprehensive, multiyear sample of U.S. public firms, we find strong support for our hypotheses. We demonstrate the robustness of our findings through the use of a difference‐in‐differences analysis on a subsample of firms that experienced exogenous changes in board gender composition as a result of director deaths . Copyright © 2014 John Wiley & Sons, Ltd.